US-Gulf AI deals usher in new era: Riyadh and Abu Dhabi are turning to AI to preserve their energy hub status. - AGUINALDO, JENNIFER (MEED Business Review, 2025)
The article discusses significant developments in artificial intelligence (AI) initiatives in the Gulf region, particularly focusing on a major AI campus project in Abu Dhabi and investments in Saudi Arabia. The UAE is set to establish a 5GW AI campus, with an estimated capital expenditure of $50 billion, in collaboration with several US companies, including Nvidia and AMD, which are also investing in AI compute capacity in Saudi Arabia. Meanwhile, Saudi Arabia's construction market is experiencing a downturn, with a reported 19% drop in capital expenditure and a 50% decrease in contract awards in early 2025, leading to uncertainty in project prioritization. The article highlights the Gulf states' aim to maintain their status as global energy hubs while transitioning to clean energy and innovation.